Lov kot kreacija bivanjskega prostora - Polanc-Podpečan, Gizela (Slavistična revija, 2004)
Lutman's novel Lov (Hunt) reveals the tragic reality of the world "abandoned by the gods". Upon the fall of the mythical into oblivion, the living space became the creation of the rational of the historical subject. An alienated space with several cosmic ties, reliably sliding towards the cataclysm. The historical subject, called "the hunter" by Lutman, decided his own fate with his violent intervention into cosmic order, as his hunt leads into self-destruction when the role of the hunter is combined with the role of the victim in the horrible reality of omophagy.
Keywords: geomantika; literarne študije; Lutman, Andrej: Lov; metaforika; simbolika; Slovene literature; slovenska književnost